Final performance evaluation report of the Regional Strategic Analysis and Knowledge Support System (ReSAKSS) - Tisch, Sarah; Marotta, Dennis; Mandolini-Trummel, Julie; Jones-Casey, Kelsey; Social Impact, Inc. (United States Agency for International Development, 2015)
This evaluation centers on how stakeholders experience ReSAKSS work at the country level. Much like looking at an open umbrella from the handle up, the perspective is of how stakeholders experience ReSAKSS work at the country, regional and continental levels from their own understanding and involvement. The evaluation questions each bring this experience into focus regarding the use of information that ReSAKSS produces, how this information and interaction with ReSAKSS contribute to policy planning, and how this information is shared. This country stakeholder perspective is important as CAADP is grounded in country-led and country-owned processes and analysis.